Molecular Characterization of Promising Willow Clones Using Rapd Markers - Singh, N. B.; Choudhary, Punit; Joshi, Santosh; Srivastava, D. K.; Sharma, J. P. (Indian Forester, 2014)
Twenty-five promising willow (Salix spp.) clones were selected after nursery screening twice, collected from six countries. Genetic relatedness among the clones was estimated using RAPD markers. Out of 20 primers tested, 16 primers were selected based on the amplification of DNA. A total of 339 bands were scored of which 338 were polymorphic showing high (99.7%) rate of polymorphism. The similarity coefficient ranged from 0.71 to 0.87. These clones were grouped into six different clusters. Clone PN-733 (Salix nigra from New Zealand) appeared to be the most diverse (76 %) from rest of the genotypes on the basis of dendrogram. Maximum similarity (87%) was observed between clones SI-63-007 (S. alba from Italy) and V-99 (Salix alba X S. rubens from Croatia). RAPD analysis proved helpful for estimating the magnitude of genetic diversity at molecular level. The clustering further indicated that the geographic distribution may not be the true index of genetic diversity in willow clones. The marker system was found useful for developing unique fingerprints of three genotypes. On the basis of banding pattern RAPD’s were effectively used for molecular characterization of willow clones used in this study.